Maternal and Perinatal Complications from a Hospital-based Intra-partum Complications Registry Established in Remote Referral Hospitals of a Desert District of India - Gehani, Manish; Balasubramaniam, Sudharsanam Manni; Johnson, Avita Rose; Goklani, Ghanshyam (Indian Journal of Community Health, 2019)
Background: Despite increase in institutional deliveries, maternal and neonatal mortality has reduced slower than expected. It is important to know the reasons of maternal and perinatal deaths for doing focused efforts for reducing them. Objective: The objective of this study was to establish a system to improve estimation of maternal and perinatal complications among deliveries. Methods: The study was designed as a descriptive study. An Intrapartum Complications Registry was set up in eleven government hospitals of Bikaner. In each facility, a “champion” nurse ensured the complete documentation in case sheets and delivery register, and entered all maternal and perinatal complications into an Intrapartum Complications Register which was digitized into a registry database. The data for a six-month period in 2014 was analysed. Results: Out of 3675 women admitted to the labour rooms of the study facilities, 295 women were referred out with complications before delivery, and 3380 mothers delivered 3386 new-borns (including 6 twins). The registry documented 828 cases (22.5%) (512 mothers and 363 new-borns, 47 cases having both mother and new-born complications) with 1014 complications (535 maternal and 479 perinatal complications). The commonest maternal complications were haemorrhage (47.1%), prolonged or obstructed labour (28.4%) and hypertensive disorders (15.3%). The commonest perinatal complications were low birth weight (33.6%), birth asphyxia (18.6%) and neonatal sepsis (16.2%). No maternal or neonatal deaths occurred up to the first 48 hours. Conclusion: Intrapartum Complications Registry improved the documentation of and revealed the profile of maternal and perinatal complications in the study area.